Differences in the crista dentata structure of the ischium of third maxilliped in Astacus leptodactylus (Eschscholtz, 1823) - Harlioglu, MM (Polish Acad Sciences, Inst Systematics Evolution Animals, 2003)
The differences in the crista dentata structure of the ischium of third maxilliped in different size Astacus leptodactylus (36-80 mm carapace lenght) were investigated. The results showed that four different types of crista dentata structure and teeth number occur in the third maxillipeds of A. leptodactylus. These arc: (1) same number of teeth in the crista dentata of right and left third maxilliped, but not in the same structure, (2) different number and structure of teeth in the crista dentata of right and left third maxilliped, (3) same number and structure of teeth in the crista dentata of right and left third maxilliped, (4) same sturucture of teeth in the crista dentata of right and left third maxilliped, but not same number of irregular teeth. In conclusion, it is believed that the differences in the crista dentata structure and different tooth number of the ischium of maxilliped cause a different cutting edge and variations in the food choice of A. leptodactylus.
Keywords: crayfish; Astacus leptodactylus; third maxilliped; teeth number; structure; food choice